Feminisme Dalam Pemikiran Riffat Hassan - Abdul Mustaqim (Al-Jami'ah: Journal of Islamic Studies, 1999)
This paper discusses analytically Riffat Hassan's thoughts concerning gender issues. Hassan's ideas on the women creation, the gender equality, and the systems of polygamy and purdah are the main subjects studied therein. Mustaqim tries to find out not only what Hassan views the subjects, but also why she differs in those issues from the majority of Islamic scholars. Using a literary analysis and a historical approach, he concludes that she reinterprets several Qur'anic and hadith texts mentioning the above matters in a way differs from that of conservative 'ulamā’ in order to support feminist propaganda, and that in doing so. Riffat is very influenced by her historical settings.